The Influence of Self-Leadership and Self-Motivation on Interest in Entrepreneurship in Management Study Program Students, STIE Eka Prasetya Medan - Citra Dewi (Outline Publisher, 2022)
This study aims to determine the effect of Self Leadership on Entrepreneurial Interest at STIE Eka Prasetya, determine the effect of Self Motivation on Entrepreneurial Interest at STIE Eka Prasetya, determine the effect of Self Leadership and Self Motivation on Entrepreneurial Interest at STIE Eka Prasetya. The population is all students of the management study program STIE Eka Prasetya period 2015 to 2019. Using the Slovin formula an error rate of 10%, a total sample of 91 respondents was obtained. The results showed that the Self Leadership and Self Motivation partially have a positive and significant effect on Student Entrepreneurial Interest in management study program at STIE Eka Prasetya. The results showed that Self Leadership and Self Motivation have a positive and significant effect on Entrepreneurial Interest in STIE Eka Prasetya. The results of this study are supported by the value of R square (R2) which means that Self Leadership and Self Motivation have an effect on the Entrepreneurial Interest. While the remaining is influenced by other factors originating from outside the research model such as the availability of capital, talent, creativity, innovation, networking and communication.